8 Inherited cardiac conditions clinics in ireland: a ten year review. (16th October 2019) - Crinion, D; Sharif, Z; O' Brien, J; Mahon, N; Keaney, J; Prenderville, T; Green, A; McGorrian, C; Ward, D; Galvin, J
Abstract : Introduction: Inherited Cardiac Conditions (ICCs) have previously been shown to account for the majority of sudden cardiac deaths in the young in Ireland. It is recommended that those affected by ICCs are referred to specialised clinics that incorporate cardiology and clinical genetics. Emulating international models, two such ICCs clinics were established in Ireland approximately ten years ago. Together they accept referrals from all regions of the country. A review of these clinics will therefore provide an estimate of the number of families affected by ICCs in Ireland. This study will also elucidate the proportion of genetic testing and the spectrum of pathogenic mutations. Methods: The Family Heart Screening Clinic (FHSC) at the Mater University Hospital and the Cardiac Risk in the Young (CRY) unit at Tallaght University Hospital, are the only adult ICCs clinics in Ireland. These collaborate with National Centre of Medical Genetics and Health-in-code based in A Coruña, Spain. This study reviewed all families that attended since the clinics' foundation in 2007 until November 2017. ICCs diagnostic criteria and Sudden Adult Death Syndrome (SADS) family screening protocols as published previously. Results: A total of 10, 118 patients, comprising 4, 319 families, of which 2, 170 (50.2%) met criteria for an ICC or SADS. An overview of the family diagnoses is provided by figure 1 . Genetic testing was performed in 39% of families. A breakdown of genetic testing for cardiomyopathies and channelopathies is included in tables 1 and 2 . SADS family screening was positive in 21%, results as per figure 2 . Molecular autopsy was performed in only 4% (18/406 ), with a pathogenic mutation identified in 5 cases (2 RYR2, 1 SNC5A, 2 ANK-2). Conclusions: This ten year review provides an estimate of the prevalence and spectrum of ICCs in Ireland. Expansion of the project to include other cardiology clinics which manage such conditions would further improve accuracy. Greater utilization of genetic testing, particularly molecular autopsy is required. The yield of genetic testing for LQTS and HCM is significantly lower than widely purported figures. A higher preponderance of MYBPC3 for HCM and LMNA for DCM was observed in this Irish cohort. Rare aetiologies of note include LAMP2 and PRKAG2. SADS family screening was positive in 21%.